2019
DOI: 10.3389/fmicb.2018.03266
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Method Characterization of the Human Circulating Microbiome

Abstract: The term microbiome describes the genetic material encoding the various microbial populations that inhabit our body. Whilst colonization of various body niches (e.g., the gut) by dynamic communities of microorganisms is now universally accepted, the existence of microbial populations in other “classically sterile” locations, including the blood, is a relatively new concept. The presence of bacteria-specific DNA in the blood has been reported in the literature for some time, yet the true origin of this is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
148
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(169 citation statements)
references
References 61 publications
19
148
1
1
Order By: Relevance
“…Consistent with these findings, it was previously shown that a significant fraction of the circulating RNAs appear to originate from exogenous species and are of a rRNA origin [27]. The blood microbiome is predominated by Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes [28]. Importantly, it has been demonstrated that some of these RNAs may influence cellular activities under in vitro conditions.…”
Section: Discussionsupporting
confidence: 59%
“…Consistent with these findings, it was previously shown that a significant fraction of the circulating RNAs appear to originate from exogenous species and are of a rRNA origin [27]. The blood microbiome is predominated by Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes [28]. Importantly, it has been demonstrated that some of these RNAs may influence cellular activities under in vitro conditions.…”
Section: Discussionsupporting
confidence: 59%
“…Recent developments including multitechnical approaches [224] and more recently, contaminant-aware approaches [214,217] to evidence the existence of extra-intestinal bacteria and their relationship with metabolism point to the fact that one cannot simply repudiate the existence of tissue-specific bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…At the phylum level, we identified Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes. Once believed sterile, studies have shown healthy peripheral blood microbiomes typically include a nucleic acid signature of these phyla (5,32,46). Detection at the genus level produced a larger set of taxa, many of which (12 of 20) had inferred abundance significantly associated (FDR < 5%) with at least one host-related variable.…”
Section: Discussionmentioning
confidence: 99%
“…Repurposing read data from human sequencing studies that do not map to the human genome may reveal the microbiome, in parallel with the primary study. A possible application of this principle involves unmapped RNA-sequencing data (6,31,32), with detection via PathSeq (33), the microbial discovery pipeline for sequencing data available in the Genome Analysis Toolkit (GATK).…”
Section: Introductionmentioning
confidence: 99%